A low-cost uniaxial cell stretcher for six parallel wells - Kah, Delf-Thorge Eric; Winterl, Alexander; Přechová, Magdalena; Schöler, Ulrike; Schneider, Werner; Friedrich, Oliver; Gregor, Martin; Fabry, Ben (HardwareX, 2021)
Cells in the lungs, the heart, and numerous other organs, are constantly exposed to dynamic forces and deformations. To mimic these dynamic mechanical loading conditions and to study the resulting cellular responses such as morphological changes or the activation of biochemical signaling pathways, cells are typically seeded on flexible 2D substrates that are uniaxially or biaxially stretched. Here, we present an open-source cell stretcher built from parts of an Anet A8 3D printer. The cell stretcher is controlled by a fully programmable open-source software using GCode and Python. Up to six flexible optically clear substrates can be stretched simultaneously, allowing for comparative multi-batch biological studies including microscopic image analysis. The cell yield from the cell culture area of 4 cm2 per substrate is sufficient for Western-blot protein analysis. As a proof-of-concept, we study the activation of the Yes-associated protein (YAP) mechanotransduction pathway in response to increased cytoskeletal tension induced by uniaxial stretching of epithelial cells. Our data support the previously observed activation of the YAP transcription pathway by stretch-induced increase in cytoskeletal tension and demonstrate the suitability of the cell stretcher to study complex mechano-biological processes.
CRIS-Team Scopus Importer:2021-01-01
Keywords: 3D printer; Cell Mechanics; Cell stretcher; Mechanosensing; Uniaxial stretch; YAP

A remote-controlled observatory for behavioural and ecological research: A case study on emperor penguins - Richter, Sebastian; Gerum, Richard; Schneider, Werner; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (Methods in Ecology and Evolution, 2018)

High-Force Magnetic Tweezers with Hysteresis-Free Force Feedback - Kah, Delf-Thorge Eric; Dürrbeck, Christopher; Schneider, Werner; Fabry, Ben; Gerum, Richard (Biophysical Journal, 2020)
Magnetic tweezers based on a solenoid with an iron alloy core are widely used to apply large forces (∼100 nN) onto micron-sized (∼5 μm) superparamagnetic particles for mechanical manipulation or microrheological measurements at the cellular and molecular level. The precision of magnetic tweezers, however, is limited by the magnetic hysteresis of the core material, especially for time-varying force protocols. Here, we eliminate magnetic hysteresis by a feedback control of the magnetic induction, which we measure with a Hall sensor mounted to the distal end of the solenoid core. We find that the generated force depends on the induction according to a power-law relationship and on the bead-tip distance according to a stretched exponential relationship. Combined, they describe with only three parameters the induction-force-distance relationship, enabling accurate force calibration and force feedback. We apply our method to measure the force dependence of the viscoelastic and plastic properties of fibroblasts using a protocol with stepwise increasing and decreasing forces. We group the measured cells in a soft and a stiff cohort and find that softer cells show an increasing stiffness but decreasing plasticity with higher forces, indicating a pronounced stress stiffening of the cytoskeleton. By contrast, stiffer cells show no stress stiffening but an increasing plasticity with higher forces. These findings indicate profound differences between soft and stiff cells regarding their protection mechanisms against external mechanical stress. In summary, our method increases the precision, simplifies the handling, and extends the applicability of magnetic tweezers.
CRIS-Team Scopus Importer:2020-06-23

Mechanical plasticity of cells - Bonakdar, Navid; Gerum, Richard; Kuhn, Michael; Spörrer, Marina; Lippert, Anna Helena; Schneider, Werner; Aifantis, Katerina E.; Fabry, Ben (Nature Materials, 2016)

micrObs – A customizable time-lapse camera for ecological studies - Winterl, Alexander; Richter, Sebastian; Houstin, Aymeric; Nesterova, Anna P.; Bonadonna, Francesco; Schneider, Werner; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (HardwareX, 2020)
Camera traps for motion-triggered or continuous time-lapse recordings are readily available on the market. For demanding applications in ecology and environmental sciences, however, commercial systems often lack flexibility to freely adjust recording time intervals, suffer from mechanical component wear, and can be difficult to combine with auxiliary sensors such as GPS, weather stations, or light sensors. We present a robust time-lapse camera system that has been operating continuously since 2013 under the harsh climatic conditions of the Antarctic and Subantarctic regions. Thus far, we have recorded over one million images with individual cameras. The system consumes 122 mW of power in standby mode and captures up to 200,000 high-resolution (16 MPix) images without maintenance such as battery or image memory replacement. It offers time-lapse intervals between 2 s and 1 h, low-light or night-time power saving, and data logging capabilities for additional inputs such as GPS and weather data.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Automated camera system; Collective behavior; Ecology; Image processing; Remote sensing; Wildlife monitoring

The desmin mutation R349P increases contractility and fragility of stem cell-generated muscle micro-tissues - Spörrer, Marina; Kah, Delf-Thorge Eric; Gerum, Richard; Reischl, Barbara; Huraskin, Danyil; Dessalles, Claire A.; Schneider, Werner; Goldmann, Wolfgang; Herrmann, Harald; Thievessen, Ingo; Clemen, Christoph S.; Friedrich, Oliver; et al. (Neuropathology and Applied Neurobiology, 2021)
Aims: Desminopathies comprise hereditary myopathies and cardiomyopathies caused by mutations in the intermediate filament protein desmin that lead to severe and often lethal degeneration of striated muscle tissue. Animal and single cell studies hinted that this degeneration process is associated with massive ultrastructural defects correlating with increased susceptibility of the muscle to acute mechanical stress. The underlying mechanism of mechanical susceptibility, and how muscle degeneration develops over time, however, has remained elusive. Methods: Here, we investigated the effect of a desmin mutation on the formation, differentiation, and contractile function of in vitro-engineered three-dimensional micro-tissues grown from muscle stem cells (satellite cells) isolated from heterozygous R349P desmin knock-in mice. Results: Micro-tissues grown from desmin-mutated cells exhibited spontaneous unsynchronised contractions, higher contractile forces in response to electrical stimulation, and faster force recovery compared with tissues grown from wild-type cells. Within 1 week of culture, the majority of R349P desmin-mutated tissues disintegrated, whereas wild-type tissues remained intact over at least three weeks. Moreover, under tetanic stimulation lasting less than 5 s, desmin-mutated tissues partially or completely ruptured, whereas wild-type tissues did not display signs of damage. Conclusions: Our results demonstrate that the progressive degeneration of desmin-mutated micro-tissues is closely linked to extracellular matrix fibre breakage associated with increased contractile forces and unevenly distributed tensile stress. This suggests that the age-related degeneration of skeletal and cardiac muscle in patients suffering from desminopathies may be similarly exacerbated by mechanical damage from high-intensity muscle contractions. We conclude that micro-tissues may provide a valuable tool for studying the organization of myocytes and the pathogenic mechanisms of myopathies.
CRIS-Team Scopus Importer:2021-12-17
Keywords: desmin; desminopathy; micro-tissue; skeletal muscle physiology; tissue engineering

Unbiased High-Precision Cell Mechanical Measurements with Microconstrictions - Lange, Janina; Metzner, Claus; Richter, Sebastian; Schneider, Werner; Spermann, Monika; Kolb, Thorsten; Whyte, Graeme; Fabry, Ben (Biophysical Journal, 2017)